Knowledge, Practice and Attitude Toward HPV Vaccines in Primary Health Nurse - Reem Mahdi Alanazy; Amthal Nawaf Alenazi; Eidah Nawaf Alenazi; Laila Habib Almutairi; Rana Zaid Albaqami; Areej Hamad Alshahrane; Randa Shaleh Alharbi; Sheikha Mohammed Aienazi; Ameerah Omar Almutairi; Haila Terakhm Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Cervical tumor is regarded as a preventable disease. Nevertheless, it is the 2nd most prevalent form of cancer worldwide, following breast tumor. Aim: To determine occurrence associated with knowledge, attitude, and practice of HPV vaccination in 1ry health nurse. Materials and methods: This meta-analysis has been conducted on 7 articles according to the guidelines by the Cochrane Collaboration reporting followed the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Main findings: Major heterogeneity was found in the meta-analysis findings (chi-p <0.001, I2 98%). in the percentage of healthcare professionals (HCW) who have previously recommended the HPV vaccine (or expressed a strong recommendation) in the investigations that were included. We observed a total MD of HCWs expressing willingness to suggest the HPV vaccine equal (0.83 [ninety-five percent CI: 0.69, 0.97]), major heterogeneity was observed among the pooled studies with chi-p <0.001, I2 1000% Conclusion: In primary healthcare settings, nurses’ knowledge, practice, and attitudes toward the HPV vaccine play a crucial role in influencing vaccination rates. This study indicates that while many primary health nurses demonstrate a positive attitude toward recommending the HPV vaccine, significant variations in their knowledge and practices exist. Nurses with a solid understanding of the benefits and safety of the HPV vaccine are more likely to recommend it, highlighting the importance of education and training in enhancing their confidence and competence in vaccine promotion.